PI-like Fuzzy Logic Position Controller Design for Electro-hydraulic Servo-actuator Based on Particle Swarm Optimization and Artificial Bee Colony Algorithms - Karam, Zeyad A. (Nahrain University College of Engineering Journal, 2017)
Electrohydraulic servo actuator mathematical model is one of the highly nonlinear hydraulic models. Electrohydraulic servo actuators used by aerospace, industrial and robotics applications for which accurate and fast performance are required in the presence of large loads or external disturbances. A servo actuator is made of a hydraulic cylinder or rotary actuator that is closely connected to an electrohydraulic servo actuator.This work focuses on modeling and simulation of electrohydraulic servo actuator that used for position control of the flight surface in a military aircraft with presence of external forces. PI-like Fuzzy Logic position intelligent Controller (FLC) is designed and simulated to control the actuator desired position during a specified time with minimum steady state error, settling time and oscillations in position response. This controller is implemented by using MATLAB Simulink and it has a settling time of 0.168 (sec). By comparison with reference [3], which has settling time of 0.341 (sec), there is enhancement by using the proposed controller in settling time about 50.733%. In addition, there is a small fluctuation around the desired position because the controller of mentioned reference does not compensate the force effect and nonlinearities in the actuator model. Particle Swarm Optimization (PSO) and Artificial Bee Colony (ABC) algorithms are used for tuning the gains of the PI-like Fuzzy Logic position Controller to satisfy the minimization in position error at the presence of the external force. The results show that the performance of ABC is more efficient than of PSO algorithm, because the trials by PSO have minimal fitness of 0.0008, but by ABC the minimal fitness achieved is 0.00072.